System Identification-Enhanced Visualization Tool for Infrastructure Monitoring and Maintenance - Singh, Premjeet; Sadhu, Ayan (Frontiers in Built Environment, 2020)
Today’s complex modern infrastructure requires robust and autonomous condition assessment as they continue to age with increasing operational loads and extreme climatic events. Structural Health Monitoring (SHM) has recently gained significant interests in inspection and maintenance of large-scale structures. However, large amount of raw data resulting from the data logger of these SHM systems require appropriate tools to systematically visualize and diagnose the data. Building Information Modelling (BIM) is a powerful data management tool that can be utilized as a base platform to analyze and visualize long-term SHM data. Current BIM-based approaches have the capabilities of facilitating design, production, and construction management of structures. BIM models in such approaches can serve as static information sources that contain as-built data. The objective of this paper is to take one-step forward from static towards dynamic BIM by representing and visualizing real-time SHM data. The web-based framework developed in this study features online visualization of data, real-time system identification and efficient decision-making. In this paper, a steel bridge located in London, Ontario is utilized as a case study where both BIM and SHM are integrated in a unified fashion. The proposed framework improves the visualization of SHM data and facilitates infrastructure owners in real-time tracking of critical infrastructure.